Analysis of the Development Path of Chinese Rural Characteristic Industries and Its Impact on Farmers’ Income: The Case of agriculture Industry in Zhejiang Province - Huangfu, Xinyu (International Journal of Global Economics and Management, 2025)
Promoting the growth of farmers’ income is the central task of the work of the “three rural areas”, and the development of rural specialty industries provides a new way of thinking. In this paper, we conduct semi-structured interviews and multi-stage questionnaire surveys with unequal probability sampling on farmers and workers engaged in agriculture industry in 109 administrative villages in 6 cities of Zhejiang Province, study the development path of rural specialty industries and its effect on farmers’ income, and put forward five policy recommendations.